Regulation viral RNA transcription and replication by higher-order RNA structures within the nsp1 coding region of MERS coronavirus - Terada, Yutaka; Amarbayasgalan, Sodbayasgalan; Matsuura, Yoshiharu; Kamitani, Wataru (Scientific reports, 2024)
Coronavirus (CoV) possesses numerous functional cis-acting elements in its positive-strand genomic RNA. Although most of these RNA structures participate in viral replication, the functions of RNA structures in the genomic RNA of CoV in viral replication remain unclear. In this study, we investigated the functions of the higher-order RNA stem-loop (SL) structures SL5B, SL5C, and SL5D in the ORF1a coding region of Middle East respiratory syndrome coronavirus (MERS-CoV) in viral replication. Our approach, using reverse genetics of a bacterial artificial chromosome system, revealed that SL5B and SL5C play essential roles in the discontinuous transcription of MERS-CoV. In silico analyses predicted that SL5C interacts with a bulged stem-loop (BSL) in the 3′ untranslated region, suggesting that the RNA structure of SL5C is important for viral RNA transcription. Conversely, SL5D did not affect transcription, but mediated the synthesis of positive-strand genomic RNA. Additionally, the RNA secondary structure of SL5 in the revertant virus of the SL5D mutant was similar to that of the wild-type, indicating that the RNA structure of SL5D can finely tune RNA replication in MERS-CoV. Our data indicate novel regulatory mechanisms of viral RNA transcription and replication by higher-order RNA structures in the MERS-CoV genomic RNA.